What is Consciousness? Towards a Preliminary Definition - Pereira, Alfredo [UNESP]; Ricke, Hans (Imprint Academic, 2009)
There is little or no general agreement about what researchers should focus on when studying consciousness. The most active scientific studies often use the methods of Cognitive Neuroscience and focus mainly on vision. Other aspects and contents of consciousness, namely thoughts and emotions, are much less studied, possibly leading to a biased view of what consciousness is and how it works. In this essay we describe what we call a referential nucleus, implicit in much of consciousness research. In this context, 'consciousness' refers to (partially) reportable content experienced by living individuals. We then discuss the philosophical concept of a phenomenal world and another contemporary view that conscious experience involves, besides integration of information in the brain, participation in action-perception cycles in a natural, social and cultural environment. These views imply a need to reconceptualize 'qualia' as the conscious aspect of subjective experiences, thus stating properties of consciousness that pose serious challenges to an exclusive approach via Cognitive Neuroscience, because experimental settings oversimplify conscious experiences, narrowing them to fragments correlated with measured brain activity and behaviour In conclusion we argue that a science of consciousness requires a broad interdisciplinary range of research, including qualitative methods from the Human Sciences.